A Defense of Naturalistic Naturalized Epistemology - John Lemos (Crítica)
Naturalistic naturalized epistemology combines ontological naturalism with naturalized epistemology. Ontological naturalism is the view that nothing exists other than spatio-temporal beings embedded within a space-time framework. Naturalized epistemology is a view about the nature of knowledge characterized by its commitment to externalism and the idea that knowledge consists in beliefs reliably generated by cognitive mechanisms operating in a suitable environment. Alvin Plantinga has provided a much discussed evolutionary biological argument against naturalistic naturalized epistemology. In this article I defend naturalistic naturalized epistemology by refuting Plantinga's replies to two important criticisms of his argument.